Permeability of waterproofed concrete - Gan, Hir Yam (2009)
Over the last few years, there has been an increasing interest in the study of the water permeability of concrete. One common construction practice of making concrete impermeable to water is the use of waterproofers. Many different types of concrete waterproofers are available commercially. However, the performance of these waterproofers is not well understood and there are no authoritative guidelines presently available to quantify the performance of these different types of concrete waterproofers. In view of this, a research programme was initiated to attempts to evaluate the performance of a group of different concrete waterproofers consisting of twenty-one integral admixtures, twenty-three coating agents and seven superplasticisers.